Investigating the effects of calcium carbonate and benzoic acid, corn protein sources, and a dried fermentation product in the diets of nursery pigs - Warner, Alan J. (Kansas State University, 2022)
The 3 chapters of this thesis involve 1) effects of added calcium carbonate with and without benzoic acid on weanling pig growth performance, fecal dry matter, and blood Ca and P concentrations, 2) evaluation of different corn protein sources on nursery pig growth performance and fecal dry matter, and 3) evaluation of a dried fermentation product administered through drinking water on nursery pig growth performance, fecal E. coli characterization, antibiotic usage, and mortality. Chapter 1 utilized 1,055 pigs in two experiments. In Exp. 1, 695 pigs were used in two groups to evaluate increasing calcium carbonate (CaCO₃) levels from 0 to 1.80%. Experiment 2 utilized 350 pigs to investigate the interactive effects between CaCO₃ and benzoic acid. In Exp. 2, CaCO₃ was included at 0.45, 0.90, and 1.35% with and without 0.50% inclusion of benzoic acid. In both experiments, increasing CaCO₃ in the diet decreased G:F. In Exp. 2, there was no evidence for CaCO₃ x benzoic acid interactions, but providing benzoic acid improved ADG, ADFI, and tended to improve G:F. As well, the level CaCO₃ was directly reflective of serum Ca; as CaCO₃ decreased in the diet, so did serum Ca. Chapter 2 involved 670 nursery pigs in two experiments to investigate corn co-products as replacements to specialty protein sources in the swine industry. Experiment 1 utilized 315 pigs and observed decreased growth performance when feeding 5 or 10% of corn protein sources. The second experiment utilized 355 pigs and observed that a fourth corn protein source did not influence growth performance compared to a control. Increasing this fourth corn protein source increased daily gain and feed intake, with intermediate inclusion levels having the greatest ADG and ADFI. Gain-to-feed decreased linearly with increasing this fourth corn protein. Finally, chapter 3 utilized 34,749 pigs in two experiments to evaluate a dried fermentation product administered through drinking water on nursery pig growth performance, fecal E. coli characterization, antibiotic usage, and mortality. Experiment 1 was conducted in a research setting utilizing 350 nursery pigs, where the dried fermentation product did not influence growth, antibiotic usage, fecal consistency, or E. coli presence. Experiment 2 was conducted in commercial nurseries utilizing 34,399 nursery pigs, where providing the dried fermentation product did not influence growth performance, reduced antibiotic injections, but increased nursery mortality.
Keywords: Acid binding capacity; Benzoic acid; Calcium; Calcium carbonate; Amino acid; Corn; Corn protein; Antibiotic; Diarrhea; E. coli; Euthanasia; Injections; Mortality; Growth; Nursery pig